2020
DOI: 10.1007/s10661-020-08264-8
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide bioaccumulation in epilithic biofilms as a biomarker of agricultural activities in a representative watershed

Abstract: Brazil is one of the largest consumers of pesticides in the world. The high rainfall rate and inadequate soil use and management promote the transfer of these compounds to the aquatic system. The aim of this study was to identify and quantify pesticides present in epilithic biofilms in order to evaluate the effectiveness of this matrix as a bioindicator able to discriminate areas and periods with different inputs of pesticides. Among the 25 pesticides analyzed in the biofilms, 20 compounds were detected. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Bioconcentration factors (BCFs) are valuable indices for comparing relative concentrations of pesticides in two matrices and for quantifying accumulation from ambient water. Recent studies have quantified the magnitudes of pesticide accumulation in biofilm (e.g., Mahler et al, 2020; Rheinheimer dos Santos et al, 2020), however only two other studes explored a similarly large set of pesticides and calculated bioconcentration factors (BCFs; Rooney et al, 2020; Ijzerman et al, 2023). Our study is the first to document pesticide BCFs in biofilm in a non-agricultural context.…”
Section: Resultsmentioning
confidence: 99%
“…Bioconcentration factors (BCFs) are valuable indices for comparing relative concentrations of pesticides in two matrices and for quantifying accumulation from ambient water. Recent studies have quantified the magnitudes of pesticide accumulation in biofilm (e.g., Mahler et al, 2020; Rheinheimer dos Santos et al, 2020), however only two other studes explored a similarly large set of pesticides and calculated bioconcentration factors (BCFs; Rooney et al, 2020; Ijzerman et al, 2023). Our study is the first to document pesticide BCFs in biofilm in a non-agricultural context.…”
Section: Resultsmentioning
confidence: 99%
“…Environmentally sustainable agriculture entails not only crop productivity but also environmental long-term preservation and sustainability. It is widely reported that the quality of the water and soil ecosystems have been dramatically declining lately, attributable to contaminations from industrial agriculture effluent [ 76 , 77 , 78 ]. Generally, pollution management in the water ecosystem is more complicated than the soil ecosystem, as water bodies are commonly exposed to various anthropogenic pollutants, hence complicating the identification of pollution sources [ 79 ].…”
Section: Development Of Bioindicator In Environmental Biomonitoringmentioning
confidence: 99%
“…De par leur présence ubiquiste et leur capacité à bioaccumuler un large spectre de contaminants organiques (Huerta et al, 2015 ;Fernandes et al, 2020) Les biofilms offrent aussi de nombreux avantages, notamment le fait qu'ils sont présents dans les cours d'eau tout au long de l'année. Ainsi, grâce à leur exposition continue aux conditions prévalant dans les eaux, ils peuvent renseigner sur le niveau moyen de contamination pendant et hors périodes d'épandage (Rheinheimer dos Santos et al, 2020). De même, leur composition hétérogène apporte de nombreux sites de sorption pour une large gamme de contaminants (Flemming, 1995 ;Flemming et Wingender, 2010 ;Creusot et al, 2020).…”
Section: Les Biofilms Des « éChantillonneurs Intégratifs » Des Pestic...unclassified